SHAXSNING XARAKTERI MUHIM XUSUSIYATI SIFATIDA - Dawkeeva, A.; Seytekova, G. (SCIENCE and SOCIETY, 2022)
The importance of a character trait is considered in the development of his personality and the ways of educating his good qualities.
Keywords: personality; character; symptom; complex; accentuation of character